How to become top of the class in OA - Frantsvåg, Jan Erik (UiT The Arctic University of Norway, 2017)
Presentation from PUBMET 2017, Zagreb 21st September 2017. This is the story of how a small, far-away university became good at OA, and intends to stay that way. What did we do, what worked – and what didn’t? Is there anything left for us to do? UiT The Arctic University of Norway is generally considered to be good at Open Access, at least in a Norwegian context. We are also asked for advice both from central agencies and from other institutions. So, how did we get to have such a position? And what have we learnt, that we could share with others who have ambitions to get into a similar position?